2017
DOI: 10.1038/aps.2017.136
|View full text |Cite
|
Sign up to set email alerts
|

Chip-based digital PCR as a novel detection method for quantifying microRNAs in acute myocardial infarction patients

Abstract: miRNAs have shown promise as potential biomarkers for acute myocardial infarction (AMI). However, the current used quantitative real-time PCR (qRT-PCR) allows solely for relative expression of nucleic acids and it is susceptible to day-to-day variability, which has limited the validity of using the miRNAs as biomarkers. In this study we explored the technical qualities and diagnostic potential of a new technique, chip-based digital PCR, in quantifying the miRNAs in patients with AMI and ischaemia-reperfusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Myocardial I/R injury is a pathological process that results in DNA, plasma membrane and and protein damage, contributing to severe myocardial injury and inflicting pain and damage on I/R injury victims [32]. Robinson et al have revealed that miRNAs are being studied more in depth due to their uses as potential markers for acute myocardial infarction (AMI), as some specific miRNAs may be associated with AMI and I/R injury [33]. Investigations on functional roles of miRNAs in I/R injury and ventricular remodeling may allow us to understand more as to how miRNAs affect cellular behaviors, such as cell apoptosis, fibrosis or infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial I/R injury is a pathological process that results in DNA, plasma membrane and and protein damage, contributing to severe myocardial injury and inflicting pain and damage on I/R injury victims [32]. Robinson et al have revealed that miRNAs are being studied more in depth due to their uses as potential markers for acute myocardial infarction (AMI), as some specific miRNAs may be associated with AMI and I/R injury [33]. Investigations on functional roles of miRNAs in I/R injury and ventricular remodeling may allow us to understand more as to how miRNAs affect cellular behaviors, such as cell apoptosis, fibrosis or infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, detected levels of (not only) miR-21 may depend on the method of miR measurement. For instance, miR-1 levels statistically differed between STEMI patients and patients with stable coronary artery disease when quantified using novel chip-based digital PCR whereas classical qRT-PCR was unable to reach significance [79]. Another novel method, droplet digital PCR, detected no association between miR-21 levels and ischemia-reperfusion injury in STEMI patients [80], and also did not find miR-21 as a potentially relevant marker of coronary artery disease [81].…”
Section: Role Of Mir-21 In Cardiac I/r Injurymentioning
confidence: 96%
“…Accordingly, this Special Issue of Acta Pharmacologica Sinica was planned to provide a forum for high quality original research and review articles to showcase the most recent advances in translational research and clinical practices on a wide-spectrum array of conventional as well as novel cardio-vascular biomarkers. Coverage of this Special Issue encompasses various forms of large or small molecules, such as proteins, peptides, cytokines, microRNAs, and metabolic by- This Special Issue covers a variety of pathological types of CVD, including acute myocardial infarction (AMI) [2][3][4][5] , heart failure [6] , aortic aneurysms [7,8] , carotid restenosis [9] , pulmonary arterial hypertension (PAH) [10] , and cardiac amyloidosis [11] . Several review articles provided in-depth analyses on the important diagnostic and prognostic roles of zinc [12] , oxylipins [13] , and leptin [14] in the fundamental cellular signaling and pathogenic processes in CVD and diabetes.…”
mentioning
confidence: 99%
“…Several review articles provided in-depth analyses on the important diagnostic and prognostic roles of zinc [12] , oxylipins [13] , and leptin [14] in the fundamental cellular signaling and pathogenic processes in CVD and diabetes. Notably, all the 7 original research articles are clinical research on Asian patients with AMI [5] or PAH [10] as well as European patients with AMI [2] , chronic heart failure [6] , vascular aneurysm [7] or restenosis [9] , and stroke [15] .…”
mentioning
confidence: 99%
See 1 more Smart Citation